RETRENCHMENT STRATEGY IN HUMAN RESOURCE MANAGEMENT: THE CASE OF VOLUNTARY SEPARATION SCHEME (VSS) - T. Ramayah,; Muhamad Jantan,; Chandra Mohan Krishnan, (Asian Academy of Management Journal, 2004)
One of the major challenges of business leadership in this millennium is to manage continued improvement in a competitive position. In order to stay competitive, companies are trying to become more "mean and lean". To achieve this, many major corporations have adopted the "downsizing and rightsizing" strategy. Voluntary Separation Scheme (VSS) has been a global phenomenon since the 1980's and is common particularly in larger companies. In this study, the reaction to the VSS program involving the employees of a government agency embracing privatisation was studied, specifically the influence of the basic needs and referent power on the choice of acceptance and non-acceptance of VSS. The second objective of this study was to evaluate the success or failure of the VSS from the workers perspective in particular, whether their decision met their needs. The results showed that basic needs had an influence on the acceptance and the non-acceptance of VSS, namely health needs, security needs and self-esteem needs. All the referent powers (subjective norms) had an influence, but surprisingly close friends had the strongest influence. Differences were also found between the expectations and the perception of the workers who accepted or rejected the VSS. From the workers' perspective, it appeared that the VSS carried out in this organization was not a success.